(untitled) (Fiep Bulletin - online, 2015)
Abstract: While elaborating this qualitative study of the imaginative adventure of dancing in a wheelchair, we conducted semi-structured interviews of twenty wheelchair users. The analysis of the Orlandi (1987) discourse and the free association of ideas through the use of the cue words adventure, dance, body, movement, liberty, wheelchair permitted the dancer to temporarily relive his dance experience, formulating projective, image-filled visions. This is the way opposites discover how to get in touch with one another and transform themselves. Our challenge was to explain how paralyzed bodies, through the magic of dance, the solidarity of the walking partners and the complicity of the festivities, experience a process of continuity in which the movements of the wheelchair users, walkers and wheelchairs integrate themselves into a choreographic triad, metamorphosing the handicapped person’s apparent immobility, covering it with expressions and code signs established in different languages and styles. They turn themselves into something else, into another person who, upon gaining wings, (re)assumes his place in a (con)fusion of chairs, wheels, movements, bodies and dancing objects. On the stage of life, the movements gain life, posture and bodily attitude and transform themselves into danced gestures that propagate themselves from one body to another. In the final metamorphosis, through the identification with and magic of Love, the spirit traverses the body, tasting the flavor of each movement, imprinting it with new qualities and nuances and achieving humanization in nature. Here, the narrative of the adventure of dancing on wheels causes the dancers to forget about prejudices, social values, social exclusion and dancing identity and they prepare themselves for their next flight.